(untitled) (Psychology Travelogs, 2021)
The article analyzes the features of self-destructive behavior as a form of manifestation, ritual, tradition. The main forms and ideas of self-destructive behavior in different religions and ethnic groups are described. The main personal motives of self-destructive behavior as a result of the influence of religious, philosophical, social ideas on the individual are revealed. It is revealed that in different cultures, ethnic groups, religions and philosophical concepts there are ideas, postulates that contribute to the formation of self-destructive behavior. In this case, pain, suffering, and sometimes death are seen as a benefit, as something that contributes to the development, purification of the individual or society as a whole. Self-destructive behavior as a form of ritual, tradition or philosophical concept can be found in the history of almost all ethnic groups, and some of these traditions are preserved to this day, such as sepuku, ritual self-flagellation and others. It was found that self-torture is known in different cultures and religions, can have the function of rite, tradition, worship, atonement, restoration of honor, initiation and more. Self-torture can be carried out by various methods: self-cuts, self-beating, "killing the flesh" and is always harmful not only in the form of injuries, but also the emergence of possible infections, organ dysfunction, and sometimes death. The self-destructive traditions and customs associated with longing for a dead relative, which were found in the Slavic and Caucasian peoples, are considered. It has been found that asceticism as a way of life that implies the renunciation of superfluous material goods is not self-destructive, but there are individuals and groups of people who, in addition to renunciation of superfluous material goods, practice asceticism through suicide, starvation, "killing the flesh", suicide and other self-destructive actions. Alcohol consumption has also been found to be a common form of self-destructive behavior known since ancient times, when people regularly drank beer and wine. Wine, brewing and other alcoholic beverages were common among most peoples living in modern Europe, and the tradition of drinking alcohol on major holidays persists to this day. Alcohol is also known in the rites of the Papuans of New Guinea, and in ancient Russia, people drank small sips at a large table. Almost all types of self-destructive behavior, regardless of their cultural background, are related to personal needs and interests of people, such as security, self-development, spiritual purification, etc., but ignore the need for survival, health, well-being. It is concluded that in some traditions, rites, cultures self-destructive actions were and are practiced today. All self-destructive actions are justified by moral, spiritual and social values and have sacred significance for people. Prospects for further research in the analysis of self-destructive behavior as a result of the influence of informal groups, modern sects, criminal groups, as well as the peculiarities of drug use, determining the factors of mass suicide and other forms of self-destructive behavior.